Komisi Yudisial dan Pengawasan Hakim di Indonesia - Wiriadinata, Wahyu (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2014)
The purpose of this paper was to find out the effectiveness of Judicial Commission in supervising judges in Indonesia. The research method used was a normative legal/juridical-normative method. Data obtained was analyzed by a descriptive-qualitative method. From the research results it was found that the role of Judicial Commission in supervising the judges was not implemented effectively. The reasons were, among others, the Judicial Commission has neither an authority to impose itself any administrative punishment nor an investigatory authority over those judges who allegedly have committed a crime.